AN EVALUATION OF ARTIFICIAL WILD TURKEY NESTS MONITORED BY AUTOMATIC CAMERAS - Larry D. Pharris; Robert C. Goetz (Wildlife Society Bulletin)
Abstract Artificial/dummy wild turkey nests monitored by an automatic camera system were designed to determine predator identification and characteristic methods of nest destruction. Additional experimental groups of artificial wild turkey nests permitted examination of the effects of the camera equipment and human scent on nest predation rates. Nests visited while wearing rubber boots were 2.5 times more successful and deviated significantly from nests observed while wearing leather boots. The use of automatic camera systems for nest predator identification is evaluated. Characteristic methods of nest destruction and factors affecting nesting studies are discussed.